(untitled) - Douglas, William O. (New York, 1974)
Describes William Douglas' friendship with Franklink Delano Roosevelt and his intimates in the New Deal, and shows the civilization and history of The West of Unived States
Keywords: West (United State),Phía Tây (Hoa Kỷ); Civilization,Văn hóa